A study of green space as social interaction space in Penang / Ellysha Nadia Ellmy ... [et al.] - Ellmy, Ellysha Nadia; Yusof, Ahmad Faisol; Abdul Aziz, Azhan; Mohd Zaki, Mohd Zikri (2023)
The Penang Botanical Garden is the primary study site since it examines the function of urban green spaces as sites for social interaction. Concerns have been expressed concerning the effect of growing urbanization and the disappearance of natural spaces in metropolitan areas on social interactions and overall wellbeing. The purpose of the study is to find out how well-planned green spaces may promote social interaction and enhance urban living. To collect information on visitor behavior, interactions, and perceptions, the research incorporates on-site observations, structured surveys, and semi-structured interviews. The investigation shows that the Penang Botanical Garden, thanks to its design, amenities, and peaceful atmosphere, serves as a lively location for a variety of social activities. According to research, green spaces significantly influence social bonds and community cohesion. To increase the social interaction potential of urban green spaces, the study suggests increasing accessibility, introducing a variety of facilities, including informative signage, and planning community events.